The one King Lear - Vickers, Brian 1937- (Harvard University Press, 2016)
"For over two hundred years editors were united in their decision to bring together the King Lear texts of the Quarto (1608) and the First Folio (1623) to produce a single text that was the basis for all modern productions and interpretations. In the 1980s a group of influential scholars argued that the two texts represent distinct stages in the life of King Lear, as Shakespeare revised his play in the light of theatrical performance. In The One King Lear, Sir Brian Vickers challenges this widely accepted theory, arguing that the cuts in the Quarto text, which are too insignificant to have been made to shorten the play, were in fact carried out by the printer because he had underestimated the amount of paper he would need. As for the Folio, the cuts removed passages of a reflective or descriptive nature and were probably made by the theatre company to speed up the action. At stake in this textual argument is the way Shakespeare's play is read and performed"--Publisher's information